Effect Fortification of Tuna Fish Bone Flour and Anchovy Powder with Different Concentrations on the Calcium value of Ikan Tuna Kering Kayu Canned - Laitupa, Ibnu Wahab; Husen, Azis (Sangia Research Media and Publishing, 2020)
As a province that has a very large sea area, North Maluku must be able to become a leading province in the fishery product sector. The mushrooming of fishery product processing businesses carried out by micro-industries in North Maluku is certainly very good but it must also be followed by the nutritional quality of the products produced. One type of nutrition that can be increased in processed fish is calcium, a material that can be used as a source of calcium is also easily available, such as tuna bone meal and anchovies which have a high enough calcium content. In previous research, it was found that the use of tuna fish bone meal had a high effect on the value of canned tuna with an average of 792.9 mg per 180 grams, the fortification of anchovy flour had an effect on product calcium, which averaged 83.34 mg per 180 grams and without preparation with an average calcium value of 21.6 mg per 180 mg. However, it has not been able to reveal the best and proper fortivication to increase the calcium content of the product, so it is necessary to continue with different concentrations for activation.The research started from the preparation stage, manufacturing of fortivication materials, product manufacturing, calcium testing, microbiological testing and statistical analysis, carried out with five treatments, namely without fortivication or 0% (A0), fortivication of tuna fish bone meal 3% (B1), flour. 6% tuna bones (B2), 3% anchovy flour (C1), 6% anchovy flour (C2).From the results of the study it was found that fortivication using tuna bone meal as much as 6% had a high effect on the increase in calcium content in canned tuna with an average of 7.253 ppm. Whereas fortivication using 3% and 6% anchovy flour had an effect on the increase in product calcium with an average value of 473 ppm and 790 ppm, respectively.